Religious Governance as Collaboration for the Resolution of Disgust: The Case of Protestantism in South Korea - Kim, Minah (Religions, 2022)
The pandemic enhanced disgust for the socially disadvantaged. In South Korea, hatred of the Chinese, the Shincheonji Church, sexual minorities, and migrant workers intensified during the pandemic. In this social atmosphere of fear and anxiety, Korean Protestantism turned into a representative group that promotes and spreads disgust. In particular, homophobia can be said to be led by the conservative Protestants in Korea. A secularization strategy proposed by David Martin has significant implications in resolving this disgust demonstrated by Korean Protestants. Martin asserts that Christianity should respond appropriately to the demands for the enhancement of the public good with the resources of religion that he calls secularization. This paper argues that religion-government governance can be a process and system that makes possible secularization in which religion realizes the virtues of reconciliation and hospitality beyond conflict and disgust. Among various types of governance, collaborative governance is the most appropriate for religion-government governance to resolve disgust for the socially disadvantaged. Here, collaboration means the process of pursuing the realization of the public good by creating new values beyond the actors’ interests. A case for this can be found in the collaboration between some Protestants and LGBTQIA+ rights activists and the government to support anonymous COVID-19 tests on homosexuals during the pandemic.